Dari Stereotype hingga Subordinasi Perempuan dalam Series Gadis Kretek 2023 Karya Ratih Kumala - Siti Uswatun Hasanah (J-SES : Journal of Science, Education and Studies, 2023)
This research aims to describe subordination-stereotypes due to gender inequality in the series “Gadis Kretek” by Ratih Kumala which will be broadcast on Netflix in November 2023. Potraits of woman who experience subordination and stereotypes are represented by the main character, namely Dasiyah or Jeng Yah. The type of research used is qualitative descriptive research with a feminist literary criticism approach. Based on the results of data analysis and research findings, it was concluded that in the “Gadis Kretek” series data was found regarding the existence of act of subordination stereotypes which include: Subordination is caused by the assumption that women are weak and not intelligent in thinking si they are only employed in the domestic sphere, not in the public sphere. Stereotypes were caused by the assumption that women were the source of bad luck and construction in society as well as the strong patriarchal culture at that time. The results of this research can be used as material in understanding literary works from a feminist perspective. For other research only focuses on very limited aspects, it is hoped that there will be follow-up research activities with a broader research focus.